2020
DOI: 10.22541/au.159318536.62302017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A study on the performance and emission of diesel engine with Jatropha biodiesel and its blends at different engine load

Abstract: An experimental study has been done to examine the performance and emission of a diesel engine using different blend ratios of Jatropha oil methyl ester at different engine speeds. At each speed, the engine was operated at no load, quarter, half, three quarters, and full load for different blending ratios. The performance parameters evaluated include Brake Power (BP), Brake Mean Effective Pressure (BMEP), brake specific fuel consumption (BSFC), air to fuel ratio (AFR), excess air factor, brake thermal efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…For various blends, Figure 5, illustrates the brake thermal efficiency as a function of engine brake power. The thermal efficiency of Jatropha increases with engine load, with maximum efficiency at 75% loading, which is consistent with references [25]. The thermal efficiency obviously decreases as the blend increases, which may be due to the lower calorific and volatility values, as well as the higher viscosity, resulting in poor atomization and vaporization [30].…”
Section: Volumetric Efficiencysupporting
confidence: 86%
See 4 more Smart Citations
“…For various blends, Figure 5, illustrates the brake thermal efficiency as a function of engine brake power. The thermal efficiency of Jatropha increases with engine load, with maximum efficiency at 75% loading, which is consistent with references [25]. The thermal efficiency obviously decreases as the blend increases, which may be due to the lower calorific and volatility values, as well as the higher viscosity, resulting in poor atomization and vaporization [30].…”
Section: Volumetric Efficiencysupporting
confidence: 86%
“…The Comparison of the current study and a number of other studies [25][26][27][28] using Jatropha biodiesel as fuel are shown in Figure 3. The brake thermal efficiency and carbon monoxide emissions are important characteristics that should be compared.…”
Section: Comarison Of Expermental Results With Other Refrencesmentioning
confidence: 96%
See 3 more Smart Citations